MEANINGS ON VARIOUS COOKING MANNERS IN VERB FORMS - Tito Prayogi, Dini Siamika (Lingual Journal of Language and Culture; Vol 1 No 1 (2016)DO - 10.24843/LJLC.2016.v01.i01.p04, 2016)
This paper aims at investigating the meaning of verb form ‘cook’ having one form with different manners of cooking something. Therefore, the analysis discusses about the various cooking manners in verb forms because cooking is an action or do something. The data was taken from the article about cooking procedure, by note taking technique. The data was further analyzed by natural semantics metalanguage. The result showed that verbs in cooking action have some similar meaning with different manners such as the manner cooking of blanch means cooking food into boiling water in a few minutes, while the manner cooking of steam means cooking food on the boiled water. Here, metalanguage manages to describe and analyze the verb meaning in cooking manners.
Keywords: metalanguage, verb